Employer-to-Employer Mobility and Wages in Europe and the United States - Daniel Borowczyk-Martins (Institute of Labor Economics (IZA), 2025)
I produce novel evidence on worker reallocation across employers and between employment and nonemployment/unemployment for several European countries over the past two decades. I construct a dataset of monthly transition rates by developing a novel approach to measure them using cross-sectional data from the European Union Labor Force Survey. Transition rates exhibit similar cyclical patterns across countries, but their levels are persistently different. I compute an indicator of the pace of worker reallocation up the job ladder, and find that it varies substantially across countries, is pro-cyclical, and exhibits a systematic positive relationship with wage inflation.
Keywords: E24; E32; J63; 330; labor market flows; job ladder; business cycles; wage inflation; Phillips curve